2022
DOI: 10.1186/s12960-022-00776-3
|View full text |Cite
|
Sign up to set email alerts
|

Job strain and burnout in Spanish nurses during the COVID-19: resilience as a protective factor in a cross-sectional study

Abstract: Background Nurses are frequently exposed to chronic stress in the workplace generating harmful effects such as job strain and burnout. On the contrary, resilience has been shown to be a beneficial variable. The objective of this study was to analyze the relationship between dimensions of the Job Demand Control-Support model, resilience and burnout in nurses, and examine the mediating role of resilience between job strain and burnout. Methods A desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
(67 reference statements)
1
11
0
1
Order By: Relevance
“…They discuss that the experienced social support helped the teachers cope with the changes and uncertainty the pandemic brought and made them more satisfied with their job even in the stressful, new situation. Similar link between job strain and burnout during the COVID-19 pandemic was found for nurses (18).…”
Section: The Effects Of the Restrictions To Parents' Workloadsupporting
confidence: 72%
See 2 more Smart Citations
“…They discuss that the experienced social support helped the teachers cope with the changes and uncertainty the pandemic brought and made them more satisfied with their job even in the stressful, new situation. Similar link between job strain and burnout during the COVID-19 pandemic was found for nurses (18).…”
Section: The Effects Of the Restrictions To Parents' Workloadsupporting
confidence: 72%
“…In previous research about the COVID-19 pandemic, Karasek's model has been utilized mostly when investigating the strain experienced by healthcare workers and teachers [e.g., (16)(17)(18)]. The increased demands at work during the COVID-19 pandemic have been confirmed to predict increased feelings of burnout for Spanish teachers (17).…”
Section: The Effects Of the Restrictions To Parents' Workloadmentioning
confidence: 99%
See 1 more Smart Citation
“…The high workload, unsafe workplace, and lack of training resulted in increased job stress [54,55]. The study conducted by Molero et al based on the JDC model also found that nurses' work stress surged during the COVID-19 pandemic, and even led to job burnout [47]. Therefore, we presume that COVID-19 event strength may be able to in uence PHC medical staff job burnout through job stress.…”
Section: The Mediating Role Of Job Stressmentioning
confidence: 86%
“…Speci cally, the model argues that job-related stress arises when individuals experience high job demands and low job control simultaneously. Several studies have revealed that the ongoing COVID-19 pandemic imposes tremendous work demands and limited work control on medical personnel [47,48]. Consequently, the COVID-19 event strength may heighten job stress among medical personnel, leading to adverse impacts on their health and well-being [44].…”
Section: The Mediating Role Of Job Stressmentioning
confidence: 99%